Sun leaves up-regulate the photorespiratory pathway to maintain a high rate of CO2 assimilation in tobacco - Huang, Wei; Zhang, Shi-Bao; Hu, Hong (Frontiers in Plant Science, 2014)
The greater rate of CO2 assimilation in sun-grown tobacco leaves leads to lower intercellular and chloroplast CO2 concentrations and, thus, a higher rate of oxygenation of ribulose-1,5-bisphosphate (RuBP) than in shade-grown leaves. Impairment of the photorespiratory pathway suppresses photosynthetic CO2 assimilation. Here, we hypothesized that sun leaves can up-regulate photorespiratory pathway to enhance the rate of CO2 assimilation in tobacco. To test this hypothesis, we examined the responses of photosynthetic electron flow and CO2 assimilation to incident light intensity and intercellular CO2 concentration (Ci) in leaves of ‘k326’ tobacco plants grown at 95% sunlight (sun plants) or 28% sunlight (shade plants). The sun leaves had higher photosynthetic capacity and electron flow devoted to RuBP carboxylation (JC) than the shade leaves. When exposed to high light, the higher Rubisco content and lower Ci in the sun leaves led to greater electron flow devoted to RuBP oxygenation (JO). The JO/JC ratio was significantly higher in the sun leaves than in the shade leaves under strong illumination. As estimated from CO2-response curves, the maximum JO was linearly correlated with the estimated Rubisco content. Based on light-response curves, the light-saturated JO was linearly correlated with light-saturated photosynthetic electron flow and light-saturated photosynthesis. These findings indicate that enhancement of the photorespiratory pathway is an important strategy by which sun plants maintain a high rate of CO2 assimilation.